A critical discourse analysis on the discourse representation of the policy makers and the stakeholders on MBMMBI - Tharmalingam, Selvarajah; Zubairi, Ainol Madziah (Research Management Centre, International Islamic University Malaysia, 2016)
The Ministry of Education (MOE) had decided to abolish ‘The Teaching and Learning of Science and Mathematics in English’ (PPSMI) policy and replace it with a new policy ‘To Uphold Bahasa Malaysia and to Strengthen the English Language’ or better known as MBMMBI in 2012. The MBMMBI policy was implemented by MOE to ensure the usage of Malay Language as a medium of communication in all national schools and secondary schools and to ensure all students can master both Malay and English languages well and fluently. However, this decision attracted contestations among people of all walks of life. The policy makers maintained that MBMMBI is the way forward while the proponents of PPSMI stressed that it is a regressive decision. This continuous debate has subverted the smooth implementation of the new policy. The primary concern of this study is to investigate whether the implementation of MBMMBI is the precise decision in moving towards world class education. In addition, this study also aims to investigate whether the stakeholders, through their articulation, show acquiescence to the policy. The study employs the ethnographic research method to elicit data. The discourse representation of the policy makers will be collected from three different newspapers: Utusan Malaysia, The Star and The New Straits Times and three online portals: Malaysiakini, Malaysian Insider and Free Malaysia Today, while the discourse representation of the stakeholders will be elicited through interviews. In order to accomplish a logical conclusion for the study, the researcher uses the deductive research approach. The Critical Discourse Analysis (CDA) is used to examine the ‘discourse representation’ of the policy makers and the stakeholders in determining the future direction of the MBMMBI policy. Specifically, the study applies Wodak’s Discourse Historical Approach and Fairclough’s Discourse Representation research frameworks to analyse the data. This research is significant in revealing the flaws in the implementation of the policy and contributes recommendations to overcome any weaknesses in the policy. The research is also expected to provide a clear guideline for the government, academics and the general public in charting a clear direction for the policy.